2023
DOI: 10.2340/actadv.v103.5351
|View full text |Cite
|
Sign up to set email alerts
|

Severe Scabies: A French Multi-centre Study Involving 95 Patients with Crusted and Profuse Disease and Review of the Literature

Abstract: The aim of this multi-centre French retrospective study was to identify severe, i.e. crusted and profuse, scabies patients. Records were retrieved from 22 Dermatology or Infectious Diseases departments in the Ile-de-France from January 2009 to January 2015 to characterize epidemiology, demography, diagnosis, contributing factors, treatment features, and outcomes in severe scabies. A total of 95 inpatients (57 crusted and 38 profuse) were included. A higher number of cases was observed among elderly patients (&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In a study by Skayem et al, half of 95 severe scabies cases were initially misdiagnosed, with the most common misdiagnosis being eczema. 17 In our study, almost all patients received one or multiple misdiagnosis of eczema, with 22 patients receiving antihistamines and 18 using topical glucocorticoids as treatments. The use of glucocorticoids in scabies can exacerbate or mask the manifestations, increasing the risk of infection or severe scabies.…”
Section: Discussionmentioning
confidence: 82%
“…In a study by Skayem et al, half of 95 severe scabies cases were initially misdiagnosed, with the most common misdiagnosis being eczema. 17 In our study, almost all patients received one or multiple misdiagnosis of eczema, with 22 patients receiving antihistamines and 18 using topical glucocorticoids as treatments. The use of glucocorticoids in scabies can exacerbate or mask the manifestations, increasing the risk of infection or severe scabies.…”
Section: Discussionmentioning
confidence: 82%
“…It affects an estimated 200 million people worldwide [1,2]. In 2017, the World Health Organization (WHO) included scabies in its list of neglected tropical diseases [3]. Several studies reported a marked increase in scabies cases in Europe [4] and worldwide [5][6][7] during the coronavirus 2019 (COVID-19) pandemic, and another study observed a postpandemic rise in cases due to diagnostic delay [8].…”
Section: Introductionmentioning
confidence: 99%
“…Scabies is currently a global health problem that affects people of all ages, including children [10,11]. The incidence is particularly high in children aged under two years (infants) [3,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of a scabies infestation is usually made from the history and examination of the affected person. It is important to make a correct differential diagnosis with common skin problems that have symptoms similar to scabies (e.g., eczema, prurigo, drug-related eruptions, and psoriasis), which are usually treated with topical corticosteroids, since the administration of topical corticosteroids significantly worsens the state of the disease [ 10 ]. A definite diagnosis is established by examining the mites, eggs, or feces under a microscope after scraping the lesions with a scalpel blade and mixing them with a mineral oil solution (detection rates vary from 10 to 70%) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%